Mutual Funds Investors Behaviour in Delhi (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2017)
Investing is a very fascinating activity that captivates people from any field whether they are from business background or have low or high status in society and whatever be the level of knowledge they possess. A person with more money will have more consumption and thus he will invest in share or securities or will deposit in his bank account to get high returns to fulfill its current needs. The companies with the extra money invest in their business to expand or start with the new venture. All these activities contribute towards "investment". Mutual Fund is one of these investment opportunities that most of the people invest in. It is one of the most preferred financial instruments that give higher returns to the investor. The Mutual Fund came into existence back in year 1964 when Unit Trust oflndia was assimilate as Statutory Corporation. When UTI is incorporated, it enjoyed monopoly powers in year 1963 as it was established by the Central bank i.e., Reserve Bank Of India(RBI).The first scheme launched by Unit Trust of India(UTI) in 1964 is by the name of "Unit scheme", which had attracted many potential investors in single investment scheme. The first bank that introduces the concept of mutual fund was State Bank of India (SBI) which was recognized by the name "SBI Mutual Fund" in July, 1987
Keywords: fascinating; possess.; account